L’impact de la dictée négociée sur l’amélioration de l’orthographe Cas des élèves de la 1ère année moyenne - عريبي آية; كويزي آية (University of Eloued جامعة الوادي, 2025)
من خلال هذا البحث ، تناولنا موضوعًا مهمًا للغاية يتعلق بتأثير الإملاء التفاوضي على تحسين مهارات التهجئة لدى طلاب الصف الأول المتوسط ، لتسهيل المهمة وتصحيح الأخطاء الإملائية . ولأغراض هذا البحث ، اخترنا استبيانًا موجهًا إلى معلمي المرحلة المتوسطة لجمع البيانات حول موضوع البحث . يندرج عملنا في إطار تعليم الكتابة، وبعد تفسير النتائج، وجدنا أن تقنية الإملاء التفاوضي فعالة في تحسين التهجئة وتحفيز مهارات الكتابة لدى الطلاب. Through this research work, we have dealt with a very important theme that is interested in the implication of negotiated dictation in order to improve spelling among first year middle school students, to facilitate the task and to remedy spelling errors, for this research we opted for a questionnaire intended for middle school teachers in order to collect data on the question under research. Our work is part of the didactics of writing, and after the interpretation of the results, we find that the technique of negotiated dictation is effective for improving spelling and motivating written skills among students.
Master. Didactique et Langues appliquée.2025
Keywords: Didactics of writing; negotiated dictation; spelling; improvement; motivation. تعليم الكتابة، الإملاء التفاوضي، التهجئة، التحسين، التحفيز